2013
DOI: 10.1007/s12272-013-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment and discrimination of the roots of Cynanchum auriculatum and Cynanchum wilfordii by HPLC–UV analysis

Abstract: Cynanchum auriculatum and Cynanchum wilfordii are widely used as folk medicine in Eastern Asia. However, the indeterminacy in the authentic original plant material has resulted in the same appellative name being given to the two plants, and they are commonly misused. Therefore, it is necessary to establish an analytical method for discrimination as well as quality control of the two species. This study was to develop HPLC-UV methods for quality assessment of C. auriculatum and C. wilfordii and discrimination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…wilfordii and C . auriculatum . Moreover, genotype analysis involving real‐time PCR amplification can easily, quickly and accurately distinguish the two species …”
Section: Authentication and Adulteration By Food Categorymentioning
confidence: 99%
“…wilfordii and C . auriculatum . Moreover, genotype analysis involving real‐time PCR amplification can easily, quickly and accurately distinguish the two species …”
Section: Authentication and Adulteration By Food Categorymentioning
confidence: 99%
“…The components of CWR are as follows: cynandione A [19], cynanoneside B, p-hydroxyacetophenone, 2,5-dihydroxyacetophenone, 2,4-dihydroxyacetophenone, wilfoside K1N, wilfoside C1N [20], β -sitosterol, wilfoside C3N, methyleugenol, wilfoside C1G, cynauriculoside A, daucosterol, acetovanillone, sucrose, geniposide, succinic acid, bungeiside A [21], and cynanchone A [22]. …”
Section: Phytochemistrymentioning
confidence: 99%
“…The components of CAR are the following: cynandione A [19]; cynanoneside B; p-hydroxyacetophenone; 2,5-dihydroxyacetophenone; 2,4-dihydroxyacetophenone; wilfoside K1N; wilfoside C1N [20]; C21-steroidal glycoside [23]; cyanoauriculosides F, G, and H [24]; wilfoside C3N [25]; taraxasterol acetate; cynanchone A; succinic acid; betulinic acid; kidjoranin [25]; auriculoside A [26]; caudatin; metaplexigenin; azelaic acid; wilforibiose; sucrose; 1-O-hexadecanolenin; beta-amyrin acetate; acetylquinol; beta-sitosterol; and daucosterol [27]. …”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive constituents of Cynanchum species have been explored in a number of studies. [16][17][18] It has been reported that acetophenones, cynandione A (CA) and its derivatives, had exhibited neuroprotective and anti-tumor activities. [19][20][21] In view of the importance of acetophenones in the biological function of Cynanchum species and the fact that CA may suppress microglial activation, we investigated whether CA suppress microglial activation in LPS-stimulated BV-2 microglia.…”
mentioning
confidence: 99%